2022
DOI: 10.3390/foods11070966
|View full text |Cite
|
Sign up to set email alerts
|

Differences between Kazak Cheeses Fermented by Single and Mixed Strains Using Untargeted Metabolomics

Abstract: Mixed fermentation improves the flavor quality of food. Untargeted metabolomics were used to evaluate the impact of mixed fermentation and single-strain fermentation on the volatile and non-volatile compound profiles of Kazak cheese. Lacticaseibacillus paracasei SMN-LBK and Kluyveromyces marxianus SMN-S7-LBK were used to make mixed-fermentation cheese (M), while L. paracasei SMN-LBK was applied in single-strain-fermentation cheese (S). A higher abundances of acids, alcohols, and esters were produced via mixed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 81 publications
(86 reference statements)
0
2
0
Order By: Relevance
“…In S25%, aldehydes, alcohols, and other components accounted for 5.97%, 11.2%, and 1.06% of the total component content, respectively. Ketones in fermented milk mainly come from the β-oxidation of fatty acids [ 28 ], and the aroma of ketones becomes more intense as the carbon chain lengthens and the branched chain increases. According to previous studies, 3-hydroxy-2-butanone and 2-heptanone are sources of a creamy aroma in fermented milk.…”
Section: Resultsmentioning
confidence: 99%
“…In S25%, aldehydes, alcohols, and other components accounted for 5.97%, 11.2%, and 1.06% of the total component content, respectively. Ketones in fermented milk mainly come from the β-oxidation of fatty acids [ 28 ], and the aroma of ketones becomes more intense as the carbon chain lengthens and the branched chain increases. According to previous studies, 3-hydroxy-2-butanone and 2-heptanone are sources of a creamy aroma in fermented milk.…”
Section: Resultsmentioning
confidence: 99%
“…Comparative genomics is an effective technique to explore the changes in genomic information that occur during interspecies and intraspecies evolution ( Wassenaar and Lukjancenko, 2014 ; Huang D. et al, 2020 ). Our previous studies showed that SMN-LBK has good fermentation characteristics and probiotic properties and the ability to tolerate ethanol and ameliorate liver injury caused by ethanol in rats, but the underlying mechanism has not been clarified ( Guo et al, 2020 ; Li et al, 2022 ). Moreover, SMN-LBK has been used in commercial yogurt fermentation as an auxiliary starter, which has extremely high research value and commercial prospects.…”
Section: Introductionmentioning
confidence: 99%